St. Sophia of Kyiv Cathedral’s Millennium in Contemporary Ukrainian Historiography (A Critical Survey) - Domanovsky, А. (Харківський національний університет імені В. Н. Каразіна, 2014)
Стаття містить огляд сучасної української історіографії щодо датування заснування собору Св. Софії у Києві: 1011–1018 (теорія Нікітенко–Корнієнка), 1017 і 1037 рр. Джерела не дають жодних незаперечних підстав для датування закладення собору ні 1011, ні 1017, ні 1037 рр. Історіографічний і джерелознавчий критичний аналіз існуючих на сьогодні концепцій датування спорудження Софії Київської дозволяє висловити припущення, що будівництво собору припало на другу половину / кінець 1020-х рр. – початок / першу половину 1030-рр. Статья посвящена обзору современной украинской историографии о датировке сооружения собора Св. Софии в Киеве: 1011–1018 (теория Никитенко–Корниенко), 1017 и 1037 гг. Источники не дают никаких неопровержимых оснований для датировки основания собора ни 1011, ни 1017, ни 1037 гг. Историографический и источниковедческий анализ существующих на сегодняшний день концепций датировки сооружения Софии Киевской позволяет высказать предположение, что строительство собора пришлось на вторую половину / конец 1020-х гг. – начало / первую половину 1030-х гг. The paper is a critical survey of contemporary Ukrainian historiography about the dating for the founding of the St. Sophia Cathedral in Kyiv: 1011–1018 (Nikitenko–Kornienko theory), 1017 and 1037. The sources do not give any conclusive reasons for dating the cathedral by either 1011, or 1017, or 1037. Historiographical analysis and the critical consideration of the sources of the existing theories about the dating of the cathedral allows us to suppose that the construction of the Sophia of Kyiv took place in the second half or the end of the 1020s and the beginning or first half of the 1030s.
Keywords: Св. Софія Київська; тисячоліття; датування; огляд; історіографія; Св. София Киевская; тысячелетие; датировка; обзор; историография; St. Sophia of Kyiv; millennium; dating; survey; historiography